La caución como medio para suspender la ejecución de la sentencia al interponer recurso de casación en materia civil - Suriaga Sanabria, Cristian Alexis (2018)
The lack of an instructive that establishes the parameters that allow judges of the Provincial Court, to set properly the amount of the caution, when it is requested the suspension of the execution of the sentence, when filing an appeal of cassation by the recurrent, leaving to the free discretion of the judges to determine it; has led to the violation of constitutional rights of the litigants. Ecuador as a constitutional State of rights and justice, guarantees the fundamental rights of each and every one of its citizens; one of the main rights it guarantees is that of protection, specifically the right to legal security, which was considered for the present investigation because it was violated in the absence of the instructive, as the litigants do not have public, prior and clear knowledge about the parameters used by the judges to set the amount of the caution and therefore, when the recurrent appeal the amount to be considered excessive or insignificant, could not give an adequate motivation by the judges because the only foundation they have is that it is the exclusive power of the judge to establish the amount of the caution, violating the principle of motivation inclusive; therefore, there is a need for the Judicial Council to prepare the respective instructive…….